LANGUAGE FUNCTION IN SOCIAL LIFE AND ITS INFLUENCES - Yeni Erlita (BAHAS, 2020)
AbstractLanguage becomes a necessary thing because it helps the world having the interaction. In addition, a language is a structured system of communication used by humans. Languages consist of spoken sounds in spoken languages or written elements in written languages. There are some functions of language such as communication, the expression of identity, play, imaginative expression, and emotional release. Additionally, a language may consist of other symbolic elements like hand gestures in sign languages. Language becomes a necessary thing because it helps the world having the interaction. There are some functions of language such as communication, the expression of identity, play, imaginative expression, and emotional release. Human needs social life and social life need human. The functions of language give big impact to many aspects especially in social life. In this study, the use of language and how the function of language can give impact to society.                                                                                                   Keywords: function of language, society, system